Relaxing nonequilibrated polymers in thin films at temperatures slightly above the glass transition. Issue 6 (21st January 2017) - Chowdhury, Mithun; Al Akhrass, Samer; Ziebert, Falko; Reiter, Günter
ABSTRACT: We have studied the dewetting process of thin polystyrene films on nonwettable substrates in the viscoelastic regime slightly above the glass transition temperature. The evolution of the shape of the dewetting rim for varying film thickness, molecular weights and dewetting temperatures allowed us to determine the relaxation rates of residual stresses, which originated from nonequilibrated polymer chain conformations formed during film preparation by spin‐coating. For long chain polymers, we found rates notably faster than the longest bulk relaxation processes, highly independent of molecular weight and temperature. Our study demonstrates that dewetting is a powerful tool for sensitive characterization of nonequilibrium properties of thin polymer films. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 515–523 Abstract : Dewetting can be considered as a "nano‐rheology" experiment, which allows the measurement of the relaxation time of residual stresses for polymers of different chain lengths as a function of temperature. Residual stresses are linked with the extent of nonequilibrated chain conformations generated during film fabrication. Intriguingly, in particular for long polymer chains at temperatures slightly above the glass transition, such stresses relaxed unexpectedly fast, at rates which did not depend on chain length.